1976
DOI: 10.1677/joe.0.0680127
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Oestrogen and Gonadotrophin-Releasing Hormone on the Release and Synthesis of Luteinizing Hormone and Follicle-Stimulating Hormone From Incubated Pituitaries

Abstract: The release and synthesis of LH and FSH were studied in adenohypophyses from ovariectomized rats incubated for a period of 4 h in flasks containing 1 ml Eagle's medium. One hemipituitary was used as the experimental gland and the other half served as a control. Glands from ovariectomized untreated animals showed a spontaneous release of LH and FSH and the amount of hormones released (per mg gland) by both the hemipituitaries was not significantly different. Also the content of the hormones at the end of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
2

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
4
9
1
2
Order By: Relevance
“…As in our previous works [4,9], addition of GnRH into the incubation medium was fol lowed by time-related increases in total content of iLH (cells plus medium), these being significantly higher than control at 4 h (116%) and 5 h (118%; fig. 1 …”
Section: Effect O F Gnrh On the Kinetics O Fl H Synthesissupporting
confidence: 79%
“…As in our previous works [4,9], addition of GnRH into the incubation medium was fol lowed by time-related increases in total content of iLH (cells plus medium), these being significantly higher than control at 4 h (116%) and 5 h (118%; fig. 1 …”
Section: Effect O F Gnrh On the Kinetics O Fl H Synthesissupporting
confidence: 79%
“…Neither the negative nor the positive phase are the result of changes in pituitary LH content [1,16]. Although it has been found that oestrogen pretreatment of pituitary glands may stimulate synthesis of LH [17], our results demonstrate that LH synthesis is not obligatory for the development of the positive phase. However, further maturation of the LH polypeptide chains to the glycoprotein molecule still might play a role [18].…”
Section: Discussioncontrasting
confidence: 82%
“…In accordance with above pieces of information, the concentrations of serum and pituitary FSH in male fetuses are lower compared with female fetuses (Aubert et al, 1985;McNamara et al, 1985;Granz et al, 1997;Takeda et al, 2009). Furthermore, the magnitude of stimuli-induced FSH synthesis is lesser than that of LH synthesis, and the turnover rate of FSH is greater than that of LH (Apfelbaum and Taleisnik, 1976;Muyan et al, 1994). Such differences in expression between LH and FSH seem to explain the sex difference of the GnRH-or cAMP-mediated induction of FSHβ and the TCDD effects on them.…”
Section: Discussionsupporting
confidence: 60%